Urban Green Infrastructure for Poverty Alleviation: Evidence Synthesis and Conceptual Considerations - Shackleton, Charlie M. (Frontiers in Sustainable Cities, 2021)
The multiple benefits of urban green infrastructure (UGI) in contributing to sustainable cities are increasingly acknowledged, and yet the bulk of research over the past decade or so has focused on only a small subset of the numerous benefits, notably recreation, physical and mental health, and regulating services. In contrast, there is very little information on the contribution of UGI to several of the other Sustainable Development Goals (SDGs), and in particular SDG 1 of reducing poverty, despite the pervasiveness of poverty globally. This paper considers the diverse direct and indirect ways in which UGI can contribute to poverty alleviation, drawing on the limited evidence from various regions of the world. The direct links between UGI and poverty alleviation include provision of (1) consumptive or provisioning goods such as wild foods and firewood, (2) employment in UGI development, maintenance and restoration, and (3) land for urban agriculture, income generation and dwelling. There are also a number of indirect links via (4) cash savings through use of consumptive products from UGI, (5) improved physical and mental health, (6) improved social networks, (7) improved educational outcomes, and (8) regulation of potential natural disasters such as floods, mudslides and fires. However, the commonly unequal distribution of UGI within and between urban cities means that the poverty alleviation potential and benefits are inequitably distributed, often against those who are most need of them, i.e. the urban poor. This demands greater attention to promoting equitable distribution and quality of UGI and mainstreaming of UGI into poverty reduction strategies and programmes and vice versa.